2021
DOI: 10.1186/s12967-021-03162-0
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of colorectal cancer ligand-receptor interactions and their roles in the tumor microenvironment and prognosis

Abstract: Background Immunotherapies targeting ligand-receptor interactions (LRIs) are advancing rapidly in the treatment of colorectal cancer (CRC), and LRIs also affect many aspects of CRC development. However, the pattern of LRIs in CRC and their effect on tumor microenvironment and clinical value are still unclear. Methods We delineated the pattern of LRIs in 55,539 single-cell RNA sequencing (scRNA-seq) samples from 29 patients with CRC and three bulk R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…For instance, one study analyzed scRNA-seq and TCGA RNA-seq data of glioma cells and showed that ligands and receptors notably affect prognostic outcomes ( Yuan et al, 2019 ). Similarly, the research identified colorectal cancer subtypes based on ligand-receptor pairs (LR pairs), indicating that LR pairs are also associated with colorectal cancer immunotherapy response and prognosis ( Lin et al, 2021 ). Lung adenocarcinoma can also find Ligand-receptor interaction atlas within and between tumor cells and T cells ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, one study analyzed scRNA-seq and TCGA RNA-seq data of glioma cells and showed that ligands and receptors notably affect prognostic outcomes ( Yuan et al, 2019 ). Similarly, the research identified colorectal cancer subtypes based on ligand-receptor pairs (LR pairs), indicating that LR pairs are also associated with colorectal cancer immunotherapy response and prognosis ( Lin et al, 2021 ). Lung adenocarcinoma can also find Ligand-receptor interaction atlas within and between tumor cells and T cells ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that ligands-receptor pairs affect subtypes and the prognostic outcomes in different kinds of cancers such as glioma ( Yuan et al, 2019 ), colorectal cancer ( Lin et al, 2021 ), Lung adenocarcinoma ( Chen et al, 2020 ), and triple-negative breast cancer ( Pan et al, 2022 ). However, previous LR pairs study in melanoma was limited.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is imperative to explore a novel taxonomy to stratify stage II/III CRC patients well and determine who may truly demand or can omit ACT. Serving as the instrumental basis for the communication of cells with neighboring cells and the whole organism, LRIs exert widely divergent implications on CRC in many dimensions from the viewpoint of intercellular crosstalk 16,27,33 . Our study deciphered the heterogeneity of stage II/III CRC from the abnormal crosstalk of ligand-receptor gene pairs and proposed a promising subtyping scheme based on perturbations in LRIs.…”
Section: Discussionmentioning
confidence: 99%
“…In the progression of cancer, cancer cell-stromal cell crosstalk is orchestrated by a plethora of ligand-receptor interactions to generate a TME that favors tumor growth ( 18 ). Intercellular communication through LR pairs in the tumor microenvironment underlie the poor prognosis of multiple cancers, such as pancreatic ductal adenocarcinoma ( 19 ) and colorectal cancer ( 20 ). Increasing discoveries of receptors and ligands and their interactions has encouraged the integration of the available information on ligand-receptor interactions from many databases to facilitate research ( 21 ).…”
Section: Discussionmentioning
confidence: 99%